The effectiveness of promotional mix done by Pusat Zakat Melaka (PZM) to create customers' awareness in Melaka Tengah area in fulfilling their zakat obligation / Zurhaida Impian - Impian, Zurhaida (Faculty of Business and Management, 2008)
The purpose of this research is to know the effectiveness of promotional mix done by Pusat Zakat Melaka (PZM) to create customers' awareness in Melaka Tengah in fulfilling their Zakat obligation. The promotional mix consists of elements such as advertising, public relations direct marketing and sponsorship. Nowadays promotional mix has gained importance within the country to achieving the competitive advantage. Moreover promotional mix has been used not by the profit organization but also the nonprofit organization. The findings show that the PZM have encountered some problem in their promotional mix strategies whereby becomes one of their weaknesses strategies in order to attract the consumers. The study is to find the level of customers' awareness, the relationship between promotional mixes with customers' awareness and to determine the most effective promotional mix done by PZM. As to solve their problem, the researcher suggests some of suggestions for the company to enhancing their promotional mix strategies. A total of 80 of respondents have been asked by using questionnaire in order to gain information and feedback to the company. The questionnaire consists of questions about the promotional mix done by PZM and customer awareness in order to fulfilling their Zakat obligation.